Atrioventricular nodal reentry tachycardia treatment using CARTO 3 V7 activation mapping: a new era of slow pathway radiofrequency ablation is under coming - Chieffo, Enrico; D’Amore, Sabato; De Regibus, Valentina; Dossena, Cinzia; Frigerio, Laura; Taravelli, Erika; Ferrazzano, Carolina; De Iuliis, Pasquale; Cacucci, Michele; Landolina, Maurizio E. (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND Slow pathway (SP) ablation is the cornerstone for atrioventricular nodal reentry tachycardia (AVNRT) treatment and low-voltage bridge offers a good target during mapping using low x-ray exposure. We aimed to assess a new tool to identify SP by activation mapping using the last CARTO3® version, i.e., CARTO PRIME® V7 (Biosense Webster, Diamond Bar, CA) METHODS AND RESULTS Right atrial septum and triangle of Koch 3D-activation map were obtained from intracardiac contact mapping during low x-ray CARTO 3® procedure. In 60 patients (mean age 60.3 ± 14.7, 61 % females), undergoing ablation for AVNRT, an automatic activation map using a Decanav® mapping catheter and CARTO® Confidense™, Coherent and FAM Dx software modules were obtained. The SP was identified in all patients as the latest atrio-ventricular node (AVN) activation area; RF catheter ablation (RFCA) in that region elicitated junctional beats. The mean procedural time was 150.3 ± 48.3 minutes, the mean fluoroscopy time exposure was 2.9 ± 2 minutes, the mean dose-area patient (DAP) 16.5 ± 2.7 cGy/cm2. The mean number of RF applications was 3.9 ± 2, the mean ablation index (AI) 428.6 ± 96.6, mean contact force 8 ± 2.8 grams. There were no adverse event during the procedure and no AVNRT recurrences occurred during a mean follow-up of 14.3 ± 8.3 months. CONCLUSION Ablation of the SP by automatic mapping using Confidense™, Coherent and FAM DX software modules is an innovative, safe and effective approach to AVNRT ablation. CARTO3® V7 System shows on a 3D map the latest AV node activation area during sinus rhythm allowing low fluoroscopy time and high effective RFCA.